RSK1 is an exploitable dependency in myeloproliferative neoplasms and secondary acute myeloid leukemia - Tim Kong; Angelo B. A. Laranjeira; Christopher T. Letson; LaYow Yu; Shuyang Lin; Jared S. Fowles; Daniel A. C. Fisher; Sherwin Ng; Wei Yang; Fan He; Minyoung Youn; Kailen Mark; et al. (Nature Communications)
Abstract Myeloid malignancies are heterogenous disorders characterized by distinct molecular drivers but share convergence of oncogenic signaling pathways and propagation by ripe pro-inflammatory niches. Here, we establish a comprehensive transcriptional atlas across the spectrum of myeloproliferative neoplasms (MPN) and secondary acute myeloid leukemia (sAML) through RNA-sequencing of 158 primary samples encompassing CD34+ hematopoietic stem/progenitor cells and CD14+ monocytes. Supported by mass cytometry (CyTOF) profiling, we reveal aberrant networks of PI3K/AKT/mTOR signalling and NFκB-mediated hyper-inflammation. Combining ATAC-Seq, CUT&Tag, RNA-seq, and CyTOF, we demonstrate that targeting of ribosomal protein S6 kinase A1 (RSK1) suppresses NFκB activation and diminishes pro-inflammatory mediators including tumor necrosis factor (TNF) associated with MPN disease severity and transformation. We further evaluate a therapeutic approach utilizing a first-in-class RSK inhibitor, PMD-026, currently in Phase 2 development for breast cancer, for use in myeloid malignancies. Treatment with PMD-026 suppressed disease burden across seven syngeneic and patient-derived xenograft leukemia mouse models spanning the spectrum of driver and disease-modifying mutations. These findings uncover a therapeutic avenue for a conserved dependency across MPN and sAML.